The Effect of Low Doses of Radon on Ghrelin and Glucose Levels in Rats with Multiple Low-Dose Streptozotoccin-induced Type 2 Diabetes Mellitus - Chkheidze, Natia; Giorgadze, Elene; Nikolaishvili, Marina; Malazonia, Ana (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of our research was to identify the ghrelin concentration in experimental animals with type 2 diabetes mellitus (T2DM) and to study the effect of radon hormesis balneotherapy using natural thermal waters of Tskaltubo spring, practically, its effect on ghrelin and glucose metabolism. MATERIALS AND METHODS: To study the effect of radon in balneotherapy, group of experimental animals (multiple low doses streptozotocin-induced T2DM Wistar rats were used) went through the procedure of inhalation of radon by the Tskaltubo mineral water pool, once daily, during 10 days. In animals of the control groups, inhalation with radon was not used. The experimental group and the control group were brought from Tskaltubo to Tbilisi to the Ivane Beritashvili experimental biomedicine center, where the blood of the rats was analyzed. RESULTS: After radon inhalation therapy with Tskaltubo mineral water, a normalization of the ghrelin levels was observed in the experimental group and despite the different body weight, the levels were approximately the same and close to those of the control group. In the experimental group, ghrelin level normalization was accompanied by glycemia normalization. CONCLUSION: This research showed that Tskaltubo mineral water radon inhalation caused hormesis, which consequently decreased ghrelin levels in rodents with T2DM and obesity and the result was stable during 3 months. Ghrelin level stabilization positively influenced on glucose levels. The result of our experiment gives us a stimulus to continue future research to find more specific neurochemical mechanisms participating in radon hormesis processes and positively influencing on glucose levels and T2DM outcome.